Streamlining the Rolls Royce Supply Chain to Succeed in the 150 Seater Replacement Project - Hatta, Muhammad; Pervais, Khizer; Shi, Xi (2007)
The market value for 150 seater engines in the next 20 years will be approximately US $185 billion. Rolls Royce's market share is only around 5% of the current 150 seater market. In addition, the company is currently facing various operations and organisational issues. After considering these factors and the price elasticity demand of the 150 seater engine market, it is recommended that the company should not attempt to increase market share by competing in price but rather it should differentiate its engine and sell it at a premium price. At the same time, the company should improve its operations efficiency in order to maximise profit in the market.